The climate change influence on Indonesia medicinal plants: A review - Ngezahayo Eric; Komariah Komariah; Masykuri Mohammad (E3S Web of Conferences)
Indonesia has high biodiversity and is well-known for its medicinal plant diversity, which is both singular and globally affluent. Due to their secondary metabolite efficacy for various ailments; medicinal plants are commercially and highly useful to human. Secondary metabolites assure the plant from abiotic and biotic stressors and aid pollination and fruit distribution. However, the changing climate, deforestation, population growth, overharvesting and the unsustainable manner of medicinal plant collection for trade, may drive many populations extinct. The study aimed to review some climate change effects on Indonesian medicinal plants as potential medicine sources for discovery and human being development. By reviewing with emphasis how each of the individual factors affects the growth, development and plant secondary metabolites production. This review illustrates a common figure of environmental factors such as temperature, drought, and CO2 that affect Indonesia’s medicinal plants. It is evident that climate change is having a detrimental influence on existing resources’ life cycles, medicinal plant quality and production, habitat fragmentation, shifting distribution ranges, phenology pattern changes, etc. Compared to other commercial crops, medicinal plant research on climate change is infrequent and limited. The study suggests some different adaptive techniques be used to mitigate climatic challenges and preserve medicinal plants.